Stiffness Matters: Fine-Tuned Hydrogel Elasticity Alters Chondrogenic Redifferentiation - Bachmann, Barbara; Spitz, Sarah; Schädl, Barbara; Teuschl, Andreas H.; Redl, Heinz; Nürnberger, Sylvia; Ertl, Peter (Frontiers in Bioengineering and Biotechnology, 2020)
Biomechanical cues such as shear stress, stretching, compression and matrix elasticity are considered vital in the establishment of next generation physiological in vitro tissue models. Matrix elasticity, for instance, is known to guide stem cell differentiation, influence healing processes and modulate extracellular matrix (ECM) deposition needed for tissue development and maintenance. To better understand the biomechanical effect of matrix elasticity on formation of articular cartilage analogues in vitro, this study aimed at assessing the redifferentiation capacity of primary human chondrocytes in three different hydrogel matrices of predefined matrix elasticities. The hydrogel elasticities were chosen to represent a wide range of tissue stiffness between very soft tissues with 1 kPa Young’s modulus and perichondral-space mimicking 30 kPa elasticity. In addition, the interplay of matrix elasticity and transforming growth factor beta-3 (TGF-β3) on redifferentiation of primary human articular chondrocytes was analyzed both qualitatively (viability, morphology, histology) and quantitatively (RT-qPCR, sGAG, DNA). Results show that fibrin hydrogels of 30 kPa Young’s modulus ideally guide chondrocyte redifferentiation resulting in a native-like morphology and ECM synthesis of glycosaminoglycans (sGAG) and collagen type II. This comprehensive study sheds light on the mechanobiological impact of matrix elasticity on formation and maintenance of articular cartilage and thus represents a major step towards meeting the need for advanced in vitro tissue model to study articular cartilage regeneration and degenerative disease.